Correction to: Decline of native bees (Apidae: Euglossa ) in a tropical forest of Panama - Vega-Hidalgo, Álvaro (2021)
The article was published with a typographical error to the name Álvaro Vega-Hidalgo. The author group regrets the error and request the name recognized as it stands in this correction note and not the way it appears in the original article. Further changes were made to include the ORCID information for the contributor as well. This correction stands to correct the original article.